Structure of the gene for Xenopus transcription factor TFIIIA. - Tso, J Y (1986)
The eucaryotic transcription factor TFIIIA is required for 5S RNA transcription in Xenopus, and changes in the level of TFIIIA have been implicated in the differential expression of 5S RNA genes. In this paper, we report the isolation and sequencing of the X. laevis TFIIIA gene. The gene is approximately 11 kb in length and consists of 9 coding segments separated by 8 introns. A sequence of 30 amino acid residues is known to repeat imperfectly 9 times in tandem within the TFIIIA protein, and Miller et al. (EMBO J. 4, 1609-1614, 1985) proposed that TFIIIA evolved by duplication of a primordial 30 amino acid residue unit. Our results from DNA sequence analysis support their proposal by showing that some of the exon-intron boundaries correspond closely to the repeating unit. We also found that the 5' flanking sequence of the TFIIIA gene contains a TATA box (TATATAA) at position -32 and a CAAT box (GCCAATCC) at position -96 and that the site of polyadenylation is 255 residues 3' of the stop codon. Finally, we have shown that the coding sequence of the TFIIIA gene is significantly polymorphic.